(untitled) (Dhaka University Law Journal, 2023)
This article examines the development of minority rights and its protection system in the League of Nations. It traces the evolution of the concept of “minority” and the challenges of defining and designating it in international law. The paper also examines the content, guarantees, and implementation of the protection regime that the League of Nations established for certain minority groups in Europe, based on the treaties and instruments adopted at the 1919 Paris Peace Conference and subsequently. The article further investigates the role of the Permanent Court of International Justice and Minority Committees in interpreting and enforcing the minority rights obligations of the concerned states. In the end, the article provides a critical assessment of the achievements and shortcomings of the minority protection systems of the League and reflects on how these systems were integrated into the framework of the United Nations. Dhaka University Law Journal, Vol. 33(1), 2023 P.23-48